Los acuerdos de cooperación y los resultados empresariales: una revisión desde la metodología de eventos - Medina Salgado, Sonia; Ortiz de Urbina Criado, Marta; Sacristán Navarro, María (Cuadernos de Estudios Empresariales, 2007)
This paper examines the main empirical articles that relate firm performance and alliance strategy under the event study methodology. It explores the results differences and reviews the main factors that explain stock reaction in the studies in order to propose new directions for research.